2010
DOI: 10.1167/10.11.29
|View full text |Cite
|
Sign up to set email alerts
|

The utility of shape attributes in deciphering movements of non-rigid objects

Abstract: Most moving objects in the world are non-rigid, changing shape as they move. To disentangle shape changes from movements, computational models either fit shapes to combinations of basis shapes or motion trajectories to combinations of oscillations but are biologically unfeasible in their input requirements. Recent neural models parse shapes into stored examples, which are unlikely to exist for general shapes. We propose that extracting shape attributes, e.g., symmetry, facilitates veridical perception of non-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…The efficiency for 3-D shapes is lower than for 2-D deforming objects made of orthogonal local motions Cohen et al (2010). For 2-D objects, observers were 90 % as efficient as an optimal Bayesian decoder and even out-performed the decoder when the shapes were symmetric.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The efficiency for 3-D shapes is lower than for 2-D deforming objects made of orthogonal local motions Cohen et al (2010). For 2-D objects, observers were 90 % as efficient as an optimal Bayesian decoder and even out-performed the decoder when the shapes were symmetric.…”
Section: Discussionmentioning
confidence: 89%
“…In such cases, it is possible that information from the fovea region is weighted more than information in periphery due to a decline in stereo-acuity with eccentricity (Cumming & DeAngelis, 2001; Parker, 2007; Wardle, Bex, Cass, & Alais, 2012). Further, 2D shapes formed by visible patches can be used to extract motion as well and Cohen et al (2010) have shown that humans are not only extremely efficient at using 2D shapes but can also use abstract properties such as symmetry to extract object motion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the dynamic case, this could be related to the possibility that articulated objects are more common in the world then are objects that increase or decrease in length over a short period. The same appeal to natural statistics could be invoked to explain the difficulty in perceiving expansion or contraction in depth of solid objects (Johansson, 1964;Jansson & Johansson, 1973;Jain & Zaidi, 2011), while other deformations are easy to discern, even for rotating and flowing shapes (Cohen, Jain & Zaidi, 2010;Fantoni, Caudek & Domini, 2014;Bates et al, 2019). However, the slant illusion is just as compelling in the static case, so biases in perceiving depth versus extent from retinal images may also be in play (Jain & Zaidi, 2013;Kim & Burge 2018).…”
Section: Resultsmentioning
confidence: 97%